2021
DOI: 10.3390/nano12010050
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Textile Waste to Production of the Fibrous Antibacterial Membrane with Filtration Potential

Abstract: Wasted synthetic fabrics are a type of textile waste source; the reuse of them brings environmental protection and turns waste into a valuable material. In this work, the used nylon (polyamide) stockings were transmuted into a fine fibrous membrane via an electrospinning process. In addition, the safety antibacterial agent, monoacylglycerol (MAG), was incorporated into a recycled fibrous membrane. The results revealed that the neat, recycled polyamide (rPA) fibers with a hydrophobic surface could be converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The methods of developing antibacterial fiber include the chemical starvation technique, adding antibacterial agent into spinning solution, physical modification technique, and compound spinning technique. Post-finishing processing methods include the microcapsule method, resin finishing method, and surface coating method [ 18 ].…”
Section: Research Theories and Methodsmentioning
confidence: 99%
“…The methods of developing antibacterial fiber include the chemical starvation technique, adding antibacterial agent into spinning solution, physical modification technique, and compound spinning technique. Post-finishing processing methods include the microcapsule method, resin finishing method, and surface coating method [ 18 ].…”
Section: Research Theories and Methodsmentioning
confidence: 99%
“…(i) It may be related to an expected increased viscosity with the addition of EOs as such structures were occasionally produced at a higher concentration, i.e., at a higher viscosity of electrospun polymer solutions. Authors observed it in studies of PA11 [ 30 ], PA6 [ 31 ], or PLA/PHB [ 32 ]. (ii) The immiscibility of the EOs and the polymer solution can also play a role.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the common raw materials for electrospinning are polymers, including natural polymers, synthetic polymers, and hybrid blends [ 42 , 43 , 44 ]. Fortunately, most polymeric waste belongs to synthetic polymers such as PET, PS, PA, and so on, which can be easily electrospun into micro/nanofibers with appropriate electrospinning processing conditions [ 25 , 45 , 46 ]. Furthermore, the use of additives (such as nanoparticles) in the raw materials is feasible, leading to a wider range of material choices for recycling and utilizing plastic waste.…”
Section: Advantages Of Electrospinning For Reutilizing Polymeric Wastementioning
confidence: 99%
“…Currently, PA production is continuously growing to satisfy the requirements of applications, resulting in an important proportion of polymer waste [ 128 ]. Compared with recycled PET and EPS, there is less research about recycled PA. Janalikova et al prepared a fibrous antibacterial membrane with recycled PA and monoacylglycerol (MAG) blend by electrospinning, which also showed a filtration potential similar to electrospun PET and PS [ 46 ]. Another study by Arenas et al reported a sustainable nanofibrous sound absorption membrane with recycled PA6 and polyvinyl alcohol (PVA) by needleless electrospinning.…”
Section: Typical Polymer Waste and Reutilization Via Electrospinningmentioning
confidence: 99%